Nutritional Assessment of Patients with Liver Cirrhosis in GIT and Liver Hospital, Baghdad, 2020 - Saif M. Badr; Nawal M. Alkhalidi; Mohsin Ahmed Aldelfi; Jawad K. Al-Diwan (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Liver cirrhosis is a condition in which the liver does not function properly due to long-termdamage which is characterized by the replacement of normal liver tissue by scar tissue.Patients and Methods: Cross-sectional study to a group of patients with liver cirrhosis. The data collectionwas done between September 25 to November 2020 at the GI and Liver Center in Baghdad Medical City.Convenient sample were chosen and each one was examined individually by a questionnaire designed forthis purpose. Body wight and height was measured, body mass index (BMI) was calculated for each one ofthem.Results: The mean BMI for both genders were within normal range (25±4.86), it was higher in males(25.8±4.56) than in females (22.79±5.11). Underweight was observed in 4 cases (6.7%), Normal BMI wasrecorded in 25 (41%) of cases, overweight was seen in 20 (33.3%) of patients and 15% was obese while onlytwo patients were extremely obese (3.3%), there was no significant difference for BMI between genders.Mean energy intake was 1575.32±381.3 which had a high significant difference compared to recommendedintake.Discussion: This study had shown that mean age is (54.4±13.14). Poor nutritional status is related to worseprognosis and increases the mortality rates in liver cirrhosis, malnutrition is usual in patients and associatedwith poor outcome. Nutritional support decreases nutrition associated complication. Current study revealedthat (51.6 %) of the subjects were alcoholic. The study showed that most of the patients found to takebalanced diet (38, 63.3%) compared to patients take unbalanced diet (22, 36.7%).Conclusion: Most of the patients had malnutrition. The patients need to enhance their knowledge aboutnutrition-related issues as a part of strategies to avoid nutritional inadequacies.Patients had modified dietthat does not meet with their nutritional needs in regarding to their health status.Energy adequacy is presentin more than half had lower than recommended.